Project-Based Learning Model to Improve Students 'Ability - Susanti, Melly; Herfianti, Meiffa; Prima Monique Damarsiwi, Eska; elra perdim, Feby; Joniswan (International Journal of Psychosocial Rehabilitation, 2020)
The research was conducted to develop economic teaching materials to improve the ability and confidence of high school students in economic learning. Research is also focused on providing experience to teachers, specifically in developing teaching materials using project-based learning and applying it to learning. The method in the research to be carried out is development (research and development) and continued with quasi-experimental (quasi-experiment) collaborating with class teachers. Stages of research to be carried out, namely: (1) the preparation phase, (2) the development stage, (3) the experimental stage, and (4) evaluation. At the development stage of teaching materials using the Plomp model (2010), which includes (1) preliminary research, (2) prototyping phase, and (3) assessment phase. Furthermore, at the application stage, a collaborative experiment is carried out where the implementation of learning collaborates with the teacher. In the experimental stage, carried out by taking each of the two classes from each school as an experimental class and a control class. The results of this study are the creation of teaching materials that meet valid and practical criteria and there is an influence of teaching materials based on project learning on students' abilities and confidence